2018
DOI: 10.1016/j.actaastro.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of lean and stoichiometric air–propane mixture with a subcritical microwave streamer discharge

Abstract: Pulse detonation engines are considered to be one of effective propulsion systems for future space missions. Significant efforts are being spent on acceleration of fuel combustion and rising is efficiency. Existing studies have mainly focused on optimizing fuel injection and mixing, repetitive initiation of detonation and integration of detonation tubes with fuel inlets. Understanding of streamer propagation mechanism is of essential importance for the studies of electrical breakdown phenomena and their relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…Various types of plasma discharges have shown promising characteristics in different applications including flow control in aerodynamics [5][6][7], ignition and combustion in propulsion engineering [8][9][10][11][12][13], stabilization of flames [14][15][16][17]. Characteristic propane ignition and combustion times in the supersonic flow with Mach number 2 could be decreased up to factor 2-5 by plasma-assisted combustion [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of plasma discharges have shown promising characteristics in different applications including flow control in aerodynamics [5][6][7], ignition and combustion in propulsion engineering [8][9][10][11][12][13], stabilization of flames [14][15][16][17]. Characteristic propane ignition and combustion times in the supersonic flow with Mach number 2 could be decreased up to factor 2-5 by plasma-assisted combustion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of microwave discharges which have been realized depending on the pressure and electric intensity for different wavelengths [23][24][25][26][27]. Recent investigations have demonstrated a great potential of microwave discharges to ignite air/fuel mixtures at low-pressure [12,13]. In these applications, the discharges take the form of thin plasma filaments driven by highly non-linear ionizing waves (streamers).…”
Section: Introductionmentioning
confidence: 99%
“…Это стимулирует поиск путей практического применения такого вида разряда. Одно из возможных направленийэто поджиг горючей смеси в схемах импульсных детонационных двигателей [5].…”
Section: Introductionunclassified
“…Это стимулирует поиск путей практического применения такого вида разряда. Одно из возможных направленийэто поджиг горючей смеси в схемах импульсных детонационных двигателей [5].Газовый СВЧ разряд, зажигаемый в квазиоптическом электромагнитном (ЭМ) пучке с ТЕМ структурой поля в сантиметровом диапазоне частот f ≈ (1.5−30) GHz при газовых давлениях p, больших 10 4 Pa, и длительности СВЧ импульса τ pul в десятки микросекунд, реализуется в пространственно развитой стримерной структуре. При этом при мощности пучка P beam масштаба нескольких киловатт или даже мегаватта электрический пробой газа должен быть инициирован, например, помещением в заданную область СВЧ пучка ЭМ вибратора [6].В работе [6] полуволновый вибратор помещался на внутренней поверхности диэлектрической радиопрозрачной трубки " вдоль" вектора электрической составляющей линейно поляризованной СВЧ волны E 0 .…”
unclassified
“…Due to the use of the resonant method of amplifying the electric field, these discharges ignite at the initial field strength much lower than the breakdown energy Ecr. Detailed studies of such discharges carried out during the last 20 years at the RAS of the Russian Academy of Sciences have shown that the abovementioned method is 20 to 80 times higher in terms of energy costs than other methods, including corona discharge and spark ignition [1,2].…”
Section: Introductionmentioning
confidence: 99%